UTILIZATION OF WATER HYACINTH AS AN ENVIRONMENTALLY FRIENDLY CREATIVE ECONOMIC INDUSTRY - Rusmaniah, Rusmaniah; Arisanty, Deasy; Angriani, Parida (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Water hyacinth is often considered a harmful aquatic weed, yet it holds significant potential as a raw material for the creative industry. One such initiative has been undertaken by the community of Banyu Hirang village, where Eceng Gondok is transformed into woven products. This article aims to investigate how the utilization of Water Hyacinth contributes to an environmentally friendly creative economy in Banyu Hirang village. The research employs a qualitative approach, gathering data through in-depth interviews, observations, and documentation. Data analysis involves reduction, presentation, concluding, and final verification stages. The research findings elucidate that harnessing Water Hyacinth as a weaving material provides economic benefits for local artisans and has a positive environmental impact by reducing water weed populations and employing more eco-friendly raw materials.